2020
DOI: 10.33963/kp.15639
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure with preserved ejection fraction after the PARAGON-HF trial results: current knowledge and future directions

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…According to the available data, a significant decrease in NT-proBNP was observed in this patient [5]. Analyzing the results of the similar PARAGON-HF trial also demonstrated the positive impact of ARNI therapy in patients with preserved ejection fraction and specific clinical profiles (ejection fraction < 57% and female gender) in whom evidence-based heart failure therapy is not available [7].…”
Section: Discussionmentioning
confidence: 57%
“…According to the available data, a significant decrease in NT-proBNP was observed in this patient [5]. Analyzing the results of the similar PARAGON-HF trial also demonstrated the positive impact of ARNI therapy in patients with preserved ejection fraction and specific clinical profiles (ejection fraction < 57% and female gender) in whom evidence-based heart failure therapy is not available [7].…”
Section: Discussionmentioning
confidence: 57%
“…In Poland, HF is the most common direct cause of death. Numerous international studies showed that HF with LVEF >40% is associated with a serious prognosis [4][5][6]. In contrast to HF with reduced LVEF, treatment aimed at improving prognosis in patients with LVEF >40% has a lower class of recommendation (up to IIa), based largely on weaker evidence and/or expert opinions -in the 2021 ESC (class IIb) and 2022 ACC/ACC/HFSA (class IIa) guidelines [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure with preserved ejection fraction (HFpEF) accounts for nearly half of heart failure (HF) patients in the community, and the mortality and morbidity are high [1]. However, the established neurohormonal-based therapies, used for treating heart failure with reduced ejection fraction (HFrEF), have failed to improve exercise intolerance and provide favorable clinical outcomes for HFpEF [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the established neurohormonal-based therapies, used for treating heart failure with reduced ejection fraction (HFrEF), have failed to improve exercise intolerance and provide favorable clinical outcomes for HFpEF [2]. The study of Lelonek [1] reported that although angiotensin receptor neprilysin inhibitors (ARNIs) may benefit from treatment with HFpEF, the relevance of ARNI in HFpEF still has not been clarified.…”
Section: Introductionmentioning
confidence: 99%